FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BEI - Sofia Prima Dewi, Jusia (Jurnal Akuntansi, 2013)
The purpose of this study was to determine whether the return on asset, debt to  equity  ratio,  firm  size,  audit  opinion  and  public  accounting  firm  size  has  an influence on the timeliness of corporate financial reporting at real estate and property corporation that listed on the Indonesia Stock Exchange during the years 2008-2010. Processing the data in this study using descriptive statistics, Goodness of Fit Test, Nagelkerke's R Square Test, Hosmer and Lemeshow's Goodness of Fit Test, test the accuracy of prediction and hypothesis testing. These results indicate that the return on asset and debt to equity ratio have an influence on the timeliness of corporate financial reporting, while firm size, audit opinion and  public accounting firm size has no effect on the timeliness of corporate financial reporting.